(untitled) (Fiep Bulletin - online, 2011)
This research has the objective to identify, describe and to analyzed the areas destined to sport and leisure of the city of Novo Hamburgo/RS, with aim to determine your nature, distribution and typology, building a map of the areas already existing. The methodology used was the exploratory descriptive having as focus the areas destined to sport as leisure of Novo Hamburgo/ RS city. To the description and discussion about the results were used measures descriptive. With this research, it was identified a slight ascendence of private services about public services, with predominance of those whose the finality is associative, business and school. The public services are localized more densely in the poor neighborhood of the city, and the private services are more concentrated on the central and rural district of the city, where farm of leisure and track of racing horses was more evidenced. The most of these areas are singulars, standing out the soccer’s field and multi-sportive courts, opens and covered.